2013
DOI: 10.1103/physrevb.87.165113
|View full text |Cite
|
Sign up to set email alerts
|

Spin states of iron impurities in magnesium oxide under pressure: A possible intermediate state

Abstract: Ferropericlase, (Mg,Fe)O, is a major lower mantle mineral, and studying its properties is a fundamental step toward understanding the Earth's interior. Here, we performed a first principles investigation on the properties of iron as an isolated impurity in magnesium oxide, which is the condition of ferropericlase that iron-iron interactions could be neglected. The calculations were carried using the all-electron full-potential linearized augmented plane wave method, within the density functional theory/general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…Our calculations revealed that stable charge states for Fe in interstitial site are +3, +2 and 0, which is in good agreement with the experimental observation of stable charge states of Fe in MgO [1]. Substitutional defect formation of Fe in MgO show +3, +2, +1 and 0 as stable charge states of Fe, as has also been reported earlier [89]. As charge states of substitution doped Fe do not match with experimental observation, hence Fe atoms most likely occupy interstitial sites in MgO [1].…”
Section: G Implications For Experimentssupporting
confidence: 91%
“…Our calculations revealed that stable charge states for Fe in interstitial site are +3, +2 and 0, which is in good agreement with the experimental observation of stable charge states of Fe in MgO [1]. Substitutional defect formation of Fe in MgO show +3, +2, +1 and 0 as stable charge states of Fe, as has also been reported earlier [89]. As charge states of substitution doped Fe do not match with experimental observation, hence Fe atoms most likely occupy interstitial sites in MgO [1].…”
Section: G Implications For Experimentssupporting
confidence: 91%
“…Intermediate spin states are only metastable and thus should not be overwhelmingly present (Larico et al, 2013). For low amounts of iron (<20%) the spin transition is concentration independent, occurring between 40-60 GPa at ambient temperatures and rising to 70-125 GPa for mid-mantle temperatures (2200-2400 K) (Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…We were able to describe the XRS spectra of siderite measured within the spin crossover regime by a superposition of HS and LS reference spectra. This indicates that only parts of the single crystal crossed the spin transition and coexistence of HS and LS iron can be assumed without occurrence of iron in an intermediate 3d electronic configuration as discussed in 36 , 61 .…”
Section: Resultsmentioning
confidence: 73%
“…Next, we investigate if spectra measured within the transition region can be modeled by a simple superposition of HS and LS spectra. In that case, rather than intermediate spin states, domains with sample in LS and HS states due to pressure gradient is assumed 13 , 36 , 60 , 61 . Hence, for siderite we fitted the XRS M 2,3 - and L 2,3 -edge spectra using a HS and LS reference.…”
Section: Resultsmentioning
confidence: 99%